Reactive extraction of propionic acid Using Tri-N-butyl phosphate in petroleum ether : equilibrium study - Keshav, A. (Array, 2008)
Summary: In present paper, the recovery of propionic acid from aqueous phase by reactive extraction was studied using tri-n-butyl phosphate (TBP) in petroleum ether. Extraction using pure diluent was found to be poor. Using the mixture of extractant-diluent the extraction was significantly improved. Results were presented in terms of distribution coefficient, equilibrium complexation constant, loading ratio and extraction efficiency. Propionic acid and TBP were found to form ( = 1:1) complex with no overloadig